Molecular Docking Studies to Identify Inhibitors of Norepinephrine Reuptake from Marine Algae (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Depression is one of the major mental health problems at prevalence now days. It can be characterized by poor concentration, low self-esteem, losing interest in family or social life, feeling tired or fatigue, suicidal thoughts and similar symptoms. There are treatments like psychotherapies, antidepressants and electroconvulsive therapies available, but there is need to identify more effective treatment with lesser side effects. Marine organisms like algae, sponges or corals are been investigated to explore their potential as antidepressants. This article aims to explore the potential of some compounds from marine algae by molecular docking and assessment of pharmacokinetics. Human norepinephrine transporter (hNET) was used as target for this study as this transporter is responsible to reuptake norepinephrine and disturbs chemical balance of brain, which can be a cause for depression. Binding affinity of these compounds was compared with binding affinity of prescribed drug levomilnacipran. From 14 selected compounds, 13 showed higher binding affinity towards hNET. Among all compounds, saringosterone has highest binding score. Pharmacokinetics properties were constructive for most compounds. Compounds showed weaker druglikeness and drugs score but can be optimized to enhance it. Compounds identified as inhibitors of NET can be developed as drug molecules in future or algal source for it can be taken as a food supplement.